2019
DOI: 10.1038/s41598-019-56432-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spaceflight on the murine thymus and mitigation by exposure to artificial gravity during spaceflight

Abstract: The environment experienced during spaceflight may impact the immune system and the thymus appears to undergo atrophy during spaceflight. However, molecular aspects of this thymic atrophy remain to be elucidated. In this study, we analysed the thymi of mice on board the international space station (ISS) for approximately 1 month. Thymic size was significantly reduced after spaceflight. Notably, exposure of mice to 1 × g using centrifugation cages in the ISS significantly mitigated the reduction in thymic size.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
(59 reference statements)
1
27
0
Order By: Relevance
“…The thymus is extremely sensitive to damage and exposure to acute or chronic insults results in a pronounced decline in cellularity, a phenomenon known as thymic atrophy ( 41 , 42 ). For example, we recently demonstrated thymic atrophy displayed by mice under microgravity (0 g) conditions during spaceflight, which was partially mitigated by exposure to 1 g during spaceflight ( 43 ). After resolution of acute insults such as infections, cytoreductive therapies, and emotional and physical discomfort, the thymus is able to regenerate, although its capacity declines with age ( 41 , 42 ).…”
Section: Adult Tec Progenitors During Recovery From Stress-induced Damentioning
confidence: 99%
“…The thymus is extremely sensitive to damage and exposure to acute or chronic insults results in a pronounced decline in cellularity, a phenomenon known as thymic atrophy ( 41 , 42 ). For example, we recently demonstrated thymic atrophy displayed by mice under microgravity (0 g) conditions during spaceflight, which was partially mitigated by exposure to 1 g during spaceflight ( 43 ). After resolution of acute insults such as infections, cytoreductive therapies, and emotional and physical discomfort, the thymus is able to regenerate, although its capacity declines with age ( 41 , 42 ).…”
Section: Adult Tec Progenitors During Recovery From Stress-induced Damentioning
confidence: 99%
“…Intriguingly, space travel was shown to adversely affect T cell development in the thymus of astronauts ( Benjamin et al, 2016 ). Complementary studies involving mice aboard the International Space Station identified that the stress of microgravity led to defects in T cell development and generation in the thymus ( Horie et al, 2019 ). How space travel ultimately affects the creative process by which T cells generate their antigen recognition repertoire–the combined capacity of all individual T cell clones have in recognizing antigens–remains incompletely understood.…”
Section: The Immune System and The Creative Processmentioning
confidence: 99%
“…The study revealed that a short-term mission in space resulted in significant impact in both organs: Altered expression of genes related to T cells (e.g., Il10 , Il18bp , Il18r1 , Spp1 , Ccl7 , and IL6 ) and cancer cells (e.g., Casp8 , Fgfr2 , Figf , Hgf , Igf1 , Itga4 , Ncam1 , Pdgfa , Pik3r1 , Serpinb2 , Sykb , Cdc25a , E2f1 , Mmp9 , and Myc ). During a recent spaceflight study (35-day exposure on the ISS), researchers investigated the microgravity effects on the thymus of mice [ 72 ]. There were significant changes in gene expression, DNA fragmentation, as well as in thymus size compared with control mice, which encountered artificial 1 g acceleration by centrifugation on the ISS [ 72 ].…”
Section: Murine Experiments In the Space Environmentmentioning
confidence: 99%
“…During a recent spaceflight study (35-day exposure on the ISS), researchers investigated the microgravity effects on the thymus of mice [ 72 ]. There were significant changes in gene expression, DNA fragmentation, as well as in thymus size compared with control mice, which encountered artificial 1 g acceleration by centrifugation on the ISS [ 72 ]. The authors found a strong reduction in genes involved in the regulation of the cell cycle.…”
Section: Murine Experiments In the Space Environmentmentioning
confidence: 99%